Accelerated Reaction Engineering of Photo(bio)catalytic Reactions through Parallelization with an Open‐Source Photoreactor. Issue 10 (1st July 2021) - Winkler, Christoph K.; Simić, Stefan; Jurkaš, Valentina; Bierbaumer, Sarah; Schmermund, Luca; Poschenrieder, Silvan; Berger, Sarah A.; Kulterer, Elisa; Kourist, Robert; Kroutil, Wolfgang
Abstract: Photobiocatalysis is an alternative approach in synthesis that has received much attention in the recent years. Due to the youth of the topic, only few reactor systems are commercially available. To allow a parallel parameter‐screening approach as often used in the optimization of biocatalytic processes, a photoreactor was developed that can illuminate up to 24 samples at well‐defined reaction conditions. The device's optical features and temperature regulation have been thoroughly characterized and its application was demonstrated in four examples, specifically three photobiocatalytic and one photocatalytic process: (i) Light‐dependent decarboxylation using a photodecarboxylase; (ii) Reduction of protochlorophyllide using a protochlorophyllide oxidoreductase; (iii) Photosynthetic oxygen production performed by cyanobacteria; and (iv) (−)‐Riboflavin‐catalyzed ( E / Z )‐isomerization of cinnamic acid derivatives. Abstract : Keep an eye out : The high utility of parallel screenings of different reaction conditions for photo(bio)catalysis is demonstrated using an open‐source hardware photoreactor. Three photobiocatalytic reactions and one photoorganocatalytic reaction serve as examples: the light dependent decarboxylation of fatty acids, the reduction of protochlorophyllide to chlorophyllide, photosynthetic water splitting and isomerization of a library of cinnamic esters.